Galectin‐8 activates dendritic cells and stimulates antigen‐specific immune response elicitation - Carabelli, Julieta; Quattrocchi, Valeria; D'Antuono, Alejandra; Zamorano, Patricia Ines; Tribulatti, María Virginia; Campetella, Oscar (2018)
Galectin‐8 (Gal‐8) is a mammalian β‐galactoside‐binding lectin, endowed with proinflammatory properties. Given its capacity to enhance antigen‐specific immune responses in vivo, we investigated whether Gal‐8 was also able to promote APC activation to sustain T cell activation after priming. Both endogenous [dendritic cells (DCs)] and bone marrow‐derived DCs (BMDCs) treated with exogenous Gal‐8 exhibited a mature phenotype characterized by increased MHC class II (MHCII), CD80, and CD86 surface expression. Moreover, Gal‐8‐treated BMDCs (Gal‐8–BMDCs) stimulated antigen‐specific T cells more efficiently than immature BMDCs (iBMDCs). Proinflammatory cytokines IL‐3, IL‐2, IL‐6, TNF, MCP‐1, and MCP‐5, as well as growth factor G‐CSF, were augmented in Gal‐8–BMDC conditioned media, with IL‐6 as the most prominent. Remarkably, BMDCs from Gal‐8‐deficient mice (Lgals8−/− BMDC) displayed reduced CD86 and IL‐6 expression and an impaired ability to promote antigen‐specific CD4 T cell activation. To test if Gal‐8‐induced activation correlates with the elicitation of an effective immune response, soluble Gal‐8 was coadministrated with antigen during immunization of BALB/cJ mice in the experimental foot‐and‐mouth disease virus (FMDV) model. When a single dose of Gal‐8 was added to the antigen formulation, an increased specific and neutralizing humoral response was developed, sufficient to enhance animal protection upon viral challenge. IL‐6 and IFN‐γ, as well as lymphoproliferative responses, were also incremented in Gal‐8/antigen‐immunized animals only at 48 h after immunization, suggesting that Gal‐8 induces the elicitation of an inflammatory response at an early stage. Taking together, these findings argue in favor of the use of Gal‐8 as an immune‐stimulator molecule to enhance the adaptive immune response.